Measuring acute pulmonary responses to occupational wildland fire smoke exposure using exhaled breath condensate. Issue 2 (17th February 2020) - Wu, Chieh-Ming; Adetona, Anna; Song, Chi (Chuck); Naeher, Luke; Adetona, Olorunfemi
Abstract: Wildland firefighters are directly exposed to elevated levels of wildland fire (WF) smoke. Although studies demonstrate WF smoke exposure is associated with lung function changes, few studies that use invasive sample collection methods have been conducted to investigate underlying biochemical changes. These methods are also either unrepresentative of the deeper airways or capable of inducing inflammation. In the present study, levels of biomarkers of oxidative stress (8-isoprostane) and pro-inflammatory response (interleukin-6 [IL-6], interleukin-8 [IL-8], C-reactive protein [CRP], and soluble intercellular adhesion molecule-1 [sICAM-1]) were determined in exhaled breath condensate (EBC) samples that were collected from firefighters before, after, and next morning following prescribed burn and regular work shifts. Results show only a marginal cross-shift increase in 8-isoprostane on burn days (.05 < p value < .1), suggesting WF smoke exposure causes mild pulmonary responses.